Rhizosphere Bacteria, Rather Than Benthic Bivalve Symbionts, May Facilitate Seagrasses - Yizhou Sun; Yang Liu; Xing-Xing Cai; Mark D. Bertness; Qiang He (Ecosystem Health and Sustainability)
Seagrass beds provide critical ecosystem services, but seagrass growth can be hindered under high sulfide stress in often submerged ocean environments, particularly where nutrients are also limiting. Although symbiotic microbes associated with both bivalves and seagrass rhizospheres have been shown to oxidize sulfides and transform nitrate to ammonia that could be used by seagrasses, their relative roles in facilitating seagrasses remain poorly understood. Here, we investigated the community structure and potential functions of bacteria associated with benthic clams and surface sediments in a seagrass bed and adjacent unvegetated mudflats. We found no significant differences in the community structure of clam gill bacteria between seagrass beds and mudflats, with Spirochetes being the predominant bacterial taxa, most of which did not have known functions related to sulfur metabolism and nutrient regulation. In contrast, there were significant differences in sediment bacterial communities between seagrass beds and mudflats. The relative abundances of Proteobacteria and Bacteroidota were significantly higher in seagrass rhizospheres than in mudflats, whereas Desulfobacterota and Chloroflexi were lower. Compared to mudflats, bacteria in seagrass rhizospheres were more closely associated with sulfide oxidation and nitrate reduction, but less with sulfate reduction. These results suggest that rhizosphere bacteria, rather than clam gill bacteria, may facilitate seagrasses by oxidizing sulfide and transforming nitrate to ammonia. The lack of sulfide-oxidizing symbionts in clam gills challenges perspectives from existing lucinidae bivalve studies and suggests a more prominent role of sediment microbes. Our findings provide new insights for understanding how seagrasses can thrive in high-sulfide, low-nutrient environments.